C/EBPα Short-Activating RNA Suppresses Metastasis of Hepatocellular Carcinoma through Inhibiting EGFR/β-Catenin Signaling Mediated EMT. - Hongbo Huan; Xudong Wen; Xuejiao Chen; Lili Wu; Weihui Liu; Nagy A Habib; Ping Bie; Feng Xia (PLoS ONE, 2016)
Hepatocellular carcinoma is associated with high mortality, and tumor metastasis is an important reason for poor prognosis. However, metastasis has not been effectively prevented in clinical therapy and the mechanisms underlying metastasis have not been fully characterized. CCAAT/enhancer-binding protein-α (C/EBPα) is a transcriptional regulator with an essential role in tumor metastasis. We used short-activating RNAs (saRNA) to enhance expression of C/EBPα. Intravenous injection of C/EBPα-saRNA in a nude mouse liver orthotopic xenograft tumor model inhibited intrahepatic and distant metastasis. C/EBPα-saRNA-treated mice showed increased serum levels of albumin and decreased alanine aminotransferase (ALT), glutamic-oxalacetic transaminase (AST), indicating a role of C/EBPα in improving liver function. Migration and invasion were inhibited in hepatoma cell lines transfected with C/EBPα-saRNA. We also observed an inhibition of epithelial-mesenchymal transition (EMT) and suppression of epidermal growth factor receptor (EGFR), EGFR phosphorylation, and β-catenin in C/EBPa-saRNA-transfected cells. Our results suggested that C/EBPα-saRNA successfully inhibited HCC metastasis by inhibiting EGFR/β-catenin signaling pathway mediated EMT in vitro and in vivo.